Perinatal mortality, timing of delivery and prenatal management of monoamniotic twin pregnancy: systematic review and meta‐analysis. (5th February 2019) - D'Antonio, F.; Odibo, A.; Berghella, V.; Khalil, A.; Hack, K.; Saccone, G.; Prefumo, F.; Buca, D.; Liberati, M.; Pagani, G.; Acharya, G.
ABSTRACT: Objective: To quantify the rate of perinatal mortality in monochorionic monoamniotic (MCMA) twin pregnancies, according to gestational age, and to ascertain the incidence of mortality in pregnancies managed as inpatients compared with those managed as outpatients. Methods: MEDLINE, EMBASE and CINAHL databases were searched for studies on monoamniotic twin pregnancy. The primary outcomes explored were the incidence of intrauterine death (IUD), neonatal death (NND) and perinatal death (PND) in MCMA twins at different gestational‐age windows (24–30, 31–32, 33–34, 35–36 and ≥ 37 weeks of gestation). The secondary outcomes were the incidence of IUD, NND and PND in MCMA twins according to the type of fetal monitoring (inpatient vs outpatient), and the incidence of delivery ahead of schedule. Random‐effects model meta‐analyses were used to analyze the data. Results: Twenty‐five studies (1628 non‐anomalous twins reaching 24 weeks of gestation) were included. Single and double intrauterine deaths occurred in 2.5% (95% CI, 1.8–3.3%) and 3.8% (95% CI, 2.5–5.3%) of cases, respectively. IUD occurred in 4.3% (95% CI, 2.8–6.2%) of twins at 24–30 weeks, in 1.0% (95% CI, 0.6–1.7%) at 31–32 weeks and in 2.2% (95% CI, 0.9–3.9%) at 33–34 weeks of gestation, while there was no case of IUD, either single or double, from 35 weeks of gestation. In MCMA twin pregnancies managed mainly as inpatients, the incidence of IUD was 3.0% (95% CI, 1.4–5.2%), while the corresponding figure for those managed mainly as outpatients was 7.4% (95% CI, 4.4–11.1%). Finally, 37.8% (95% CI, 28.0–48.2%) of MCMA pregnancies were delivered before the scheduled time, due mainly to spontaneous preterm labor or abnormal cardiotocographic findings. Conclusions: MCMA twins are at high risk of perinatal loss during the third trimester of pregnancy, with the large majority of such losses occurring as apparently unexpected events. Inpatient management seems to be associated with a lower rate of mortality, although further studies are needed in order to establish the appropriate type and timing of prenatal assessment in these pregnancies. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. This article has been selected for Journal Club. Click here to view slides and discussion points.